Mecanismos de resistência de plantas daninhas ao glifosato em pomares de citros no estado de São Paulo - Amaral, Gabriel da Silva (2024)
WEED RESISTANCE MECHANISMS IN CITRUS ORCHARDS IN THE STATE OF SÃO PAULO. Citrus production, mainly concentrated in Southeast Brazil, especially in São Paulo, faces significant losses due to weed competition. Effective weed management is crucial to maintaining orchard productivity. However, the excessive use of glyphosate, the main herbicide used due to its effectiveness and affordability, has led to increased weed resistance, exacerbating the problem. The study aimed to identify and assess resistance levels in weeds present in citrus orchards in different regions of São Paulo. Resistant and susceptible seeds of Amaranthus deflexus (low amaranth), A. hybridus (purple amaranth), A. viridis (green amaranth), Bidens pilosa (blackjack), Chloris elata (feather fingergrass), Conyza bonariensis (fleabane), Digitaria insularis (sourgrass), Solanum americanum (American black nightshade), and Tridax procumbens (coat buttons) were collected from different citrus orchards, all in the state of São Paulo. Dose-response and shikimic acid accumulation experiments confirmed that the populations suspected of glyphosate resistance A. deflexus, A. hybridus, and T. procumbens exhibited herbicide susceptibility levels similar to their respective susceptible references. B. pilosa populations were also susceptible; however, there is a risk of resistance evolution. Most C. bonariensis, C. elata, and D. insularis populations evaluated showed varying levels of glyphosate resistance. The first occurrence of glyphosate resistance in the country and worldwide for A. viridis and S. americanum was identified. 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzymatic activity experiments showed that resistant populations of A. viridis, B. pilosa, C. elata, and S. americanum exhibited higher basal activity compared to their respective susceptible populations. For D. insularis, basal activity values were similar for resistant and susceptible populations. However, all resistant biotypes of these species required higher glyphosate concentrations to inhibit EPSPS by 50%, except for the R1 population of B. pilosa. Glyphosate absorption ranged from 28% to 44% between 12 to 72 hours after treatment (HAT) in A. viridis plants. Only the R2 population showed a different absorption pattern compared to the susceptible population, translocating a smaller amount of herbicide from the treated leaf to the rest of the plant and roots. Therefore, resistance in this population is attributed to lower glyphosate absorption and translocation. S. americanum plants absorbed between 35% and 50% of the herbicide up to 72 HAT. From 24 HAT, the R1 population absorbed between 10% and 15% more than the S and R2 populations. Sequencing of the conserved region of the EPSPS gene that interacts with glyphosate did not show any mutations in resistant populations of A. viridis; however, it was found that this species exhibits gene overexpression in EPSPS. In S. americanum, a double mutation was identified at positions Arg-105-Glu and Pro-106-Ser. In citrus orchards in São Paulo, multiple resistant species were identified, showing that failure to control one species can affect the control of other vulnerable species. Glyphosate resistance was identified in A. viridis and S. americanum, marking the first reported cases worldwide for these species.